Home monitoring for central apnoea. Issue 2 (February 1984) - MacKay, M; Abreu e Silva, F A; MacFadyen, U M; Williams, A; Simpson, H
Abstract : Between July 1978 and December 1981, 64 infants thought to be at increased risk from sudden infant death syndrome (SIDS) were monitored at home for central apnoea. Twenty four of the infants had had a 'near miss' episode at age, median (range), 6 (1 to 33) weeks, and of these infants 22 had had 335 alarms for apnoea by age 6 months. Stimulation by shaking was carried out on 38 occasions and bag and mask resuscitation on one. The remaining 40 infants were siblings of SIDS victims and of these, 35 were monitored from age 1 week (usually after discharge home). Thirty four of the SIDS siblings had had 573 alarms for apnoea by age 6 months: stimulation by shaking was carried out on 32 occasions and bag and mask resuscitation on one. The duration of home monitoring was, median (range), 34 (8 to 87) weeks for 'near miss' infants and 45 (12 to 70) weeks for SIDS siblings. All infants survived. As part of an over all support system monitors were accepted and greatly appreciated by most parents, especially those with previous experience of SIDS. Home monitoring was practicable but the commitment in time and expertise was great and objective benefits to the infant remain unproved.